x + 6 + 3x = 1 + 3x + 1
Combine like terms. x+3x = 4x and 1+1 = 2
4x + 6 = 3x + 2
Subtract 3x from each side
x + 6 = 2
Subtract 6 from each side
x = -4
2006-11-08 11:43:33
·
answer #1
·
answered by MsMath 7
·
4⤊
4⤋
x+6+3x= 6 1+3x+1=2 2+ 6=8
2006-11-08 13:06:23
·
answer #2
·
answered by Anonymous
·
1⤊
1⤋
x + 6 +3x = 1 + 3x + 1 (*)
Step 1 => Put together variables at left of equality sign.
=> x +6 + 3x -3x = 1 + 1
Step 2 => Put together integers at right of equality sign .
=> x + 3x -3x = 1 + 1 -6
Step 3 => Add both sides of equality sign
=> x + 0 = 2 -6
x = -4
Step 4 => Verification : Put x = -4 in (*)
We have => x + 6 + 3x = 1 + 3x + 1
-4 + 6 + 3(-4) = 1 + 3(-4) + 1
-4 + 6 -12 = 1 -12 +1
-16 + 6 = -12 + 2
-10 = -10
Answer : x = -4
2006-11-08 12:00:44
·
answer #3
·
answered by frank 7
·
0⤊
2⤋
Just do the sum and substraction of common terms. Sum all those somthing * x and all the numbers that do not have x
x + 6 + 3x = 1 + 3x + 1
4x + 6 = 2 + 3x
Move them around multiplying by -1 if you change sides
4x - 3x + 6 - 2 = 0
x + 4 = 0
x = -4
2006-11-08 11:52:43
·
answer #4
·
answered by Dr. J. 6
·
1⤊
1⤋
x+6+3x=1+3x+1
6+4x=2+3x
subtract 3x from both sides
6+x=2
subtract 6 from both sides
x=-4
2006-11-08 11:45:02
·
answer #5
·
answered by moonfreak♦ 5
·
1⤊
1⤋
,
x + 6 + 3x = 1 + 3x + 1
4x + 6 = 3x + 2
x + 6 = 2
x = -4
2006-11-09 07:09:48
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
x + 6 + 3x = 1 + 3x +1
4x + 6 = 3x + 2
x + 6 = 2
x = -4
2006-11-08 11:50:56
·
answer #7
·
answered by † NEO † 2
·
1⤊
2⤋
u just have to add and subtract to get al the x's on one side, and then all the numbers on the other side...
x + 6 + 3x = 1 + 3x + 1
6 + 4x = 2 + 3x (add like terms on each side)
4x = -4 + 3x (subtract the 6 to get x alone on the left)
x = -4 (subtract the 3x to get x alone on the left)
2006-11-08 11:45:08
·
answer #8
·
answered by Anonymous
·
1⤊
1⤋
first you have to combine like terms
x+3x-3x = 1+1-6
perform simple addition and subtraction
x = -4
2006-11-08 19:31:26
·
answer #9
·
answered by mikoch01 1
·
1⤊
1⤋
first group all those with x in the left side and the constants on the right so:
x+3x-3x=1+1-6
when you move them to the other side, change their signs..
x=-4
there, that is the answer n_n
2006-11-08 11:46:24
·
answer #10
·
answered by jamezu 2
·
1⤊
0⤋